Village Economic Revitalization Through Technology-Based OVOP Approach - Beatrice Nathania; Sarida Sirait; Arifin Tua Purba (Economics Development Analysis Journal, 2022)
The technology-based One Village One Product (OVOP) program is a program that aims to create superior village products through technology-based marketing management. This research uses qualitative analysis and produces a digital marketing application that is ready to be used by users. The stages of the research started from data reduction, data display, verification/drawing conclusions. Data design is done by making computer-based software. The software used in the application development process is XAMPP Control Panel for database management and website configuration, PhP MyAdmin to handle MySQL administration, Visual Studio Code as source-code editor in programming languages. Qualitative analysis is used to analyze technology-based applications OVOP approach in Horsik Village and the follow-up is to build digital marketing applications according to village needs. The samples and data sources for this research were village officials, farmer groups, village communities, and all parties who became data sources. The results of this study explain that the application of technology-based OVOP is very appropriate and feasible in Horsik Village. The author has re-verified the research results and conducted trials and training regarding the use of the application. The conclusion from this study is that the application of technology-based OVOP in Horsik Village has a very high chance of succeeding and improving the village economy through increasing sales of the village's superior products. The collaboration of the government, village officials, farmer groups and institutions through the results of this research will facilitate the revitalization of Horsik Village into a productive tourism village